Future explorers robots in space - Kortenkamp, Steve (North Mankato, Minnesota Capstone Press, 2016)
"Describes the use of robots in space"--
What are space robots? -- Invading Mars -- Rise of the rover robots -- Exploring other planets and moons -- Asteroids and comets -- Robots of the future
The world around us (Outer space)
Includes bibliographical references (page 47) and index
Ages 8-14
Grades 4 to 6
1 2 13
NEW_ZTN_GN
Keywords: Space probes -- Juvenile literature; Space robotics -- Juvenile literature; Outer space -- Exploration -- Juvenile literature